Morphological variability of Pocillopora damicornis in marine environmental adaptation on Sembilan Island, Sinjai District, Indonesia - RIDHA ALAMSYAH; NEVIATY P. ZAMANI; DIETRIECH G. BENGEN; I WAYAN NURJAYA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Alamsyah R, Zamani NP, Bengen DG, Nurjaya IW. 2024. Morphological variability of Pocillopora damicornis in marine environmental adaptation on Sembilan Island, Sinjai District, Indonesia. Biodiversitas 25: 3116-3124. Pocillopora damicornis (Linnaeus, 1758) is a coral species that is very plastic and allows it to adapt to environmental conditions. Pocillopora corals are important species of coral reef ecosystems, but it was not easy to interpret morphological variations and species boundaries. Morphological variation is so high that misidentification often occurs. This research aims to understand the morphological differences between apex branches, secondary branches, and primary branches at reef flat, lagoon, and reef slope sites in the waters of Sembilan Island. The results obtained, except for corallite width, corallite spacing, branch width, branch length, branch angle, and interbranch spacing, were significantly different at the apex branch, secondary branch, and primary branch. Corallite width is larger at the apex branch, while corallite spacing is very small. The largest distance between corallites is found in the secondary branches. The highest branch width is on the primary branch. Branch width on secondary branches is more consistent. The branching angle is greater in the primary branch, especially in the reef flat and reef slope. The apex branch tends to form a smaller angle. The largest interbranch spacing was found at the apex branch for all regions. Both primary and secondary branches show small variations. The morphology of P. damicornis on the reef slope is more influenced by salinity and current speed. In reef flat areas, the environmental factors that most influence coral morphology are organic matter, turbidity, TSS, and light intensity, including wave height, temperature, and pH. For the lagoon area group, there is no strong influence of environmental parameters.